Profiling the host response to malaria vaccination and malaria challenge. Issue 40 (29th September 2015) - Dunachie, Susanna; Hill, Adrian V.S.; Fletcher, Helen A.
Abstract A vaccine for malaria is urgently required. The RTS, S vaccine represents major progress, but is only partially effective. Development of the next generation of highly effective vaccines requires elucidation of the protective immune response. Immunity to malaria is known to be complex, and pattern-based approaches such as global gene expression profiling are ideal for understanding response to vaccination and protection against disease. The availability of experimental sporozoite challenge in humans to test candidate malaria vaccines offers a precious opportunity unavailable for other current targets of vaccine research such as HIV, tuberculosis and Ebola. However, a limited number of transcriptional profiling studies in the context of malaria vaccine research have been published to date. This review outlines the background, existing studies, limits and opportunities for gene expression studies to accelerate malaria vaccine research.